On my country and the world - Gorbachev, Mikhail (Columbia University Press, 2019)
"Here is the whole sweep of the Soviet experiment and experience as told by its last steward. Drawing on his own experience, rich archival material, and a keen sense of history and politics, Mikhail Gorbachev speaks his mind on a range of subjects concerning Russia's past, present, and future place in the world. Here is Gorbachev on the October Revolution, Gorbachev on the Cold War, and Gorbachev on key figures such as Lenin, Stalin, and Yeltsin. This anniversary edition features a new foreword by William Taubman, award-winning biographer of Khrushchev and Gorbachev"--